Talanoa : Share, Listen, Understand - Tapu F; Cleverley L; Manoa J; West D; Samuelu F; Camaira J; Ramacake S; Seru P; Misa G (My University, 2022)
This monograph has been titled Talanoa: Share, Listen, Understand as it lays out eight research reports shared by Massey University alumni who are proudly of i-Taukei Fijian, i-Kiribati, Samoan, Tongan, Tuvaluan, Tokelauan and Cook Island descent. The reports story the experiences and views of frontline workers who have worked alongside Pacific people, their families and their communities. The reports have been presented to encourage readers to listen to what has been shared; to see the world through the eyes of Pacific people; to identify ways to strengthen relationships with the Pacific community, thereby nurturing Pacific health and wellbeing.